The evolving locally-advanced non-small cell lung cancer landscape: Building on past evidence and experience. Issue 2 (November 2015) - Méry, Benoite; Guy, Jean-Baptiste; Swalduz, Aurélie; Vallard, Alexis; Guibert, Cyril; Almokhles, Hweej; Ben Mrad, Majed; Rivoirard, Romain; Falk, Alexander T.; Fournel, Pierre; Magné, Nicolas
Summary Lung cancer is a major public health concern worldwide. Progress in improving 5-year survival is lagging behind comparable survival rates in other common cancers. The majority of patients with locally advanced non-small cell lung cancer (NSCLC) are not suitable for surgical resection, hence the major role of radical radiotherapy. Advances in radiotherapy techniques allow targeted treatment of the disease, whilst minimizing the dose to organs at risk. Recent research into fractionation schedules, with hyperfractionated and accelerated radiotherapy regimens has been promising. Platinum-based chemotherapy has long been the standard of care for the initial treatment of advanced NSCLC. However, if radical radiotherapy remains the cornerstone of treatment for patients with unresectable advanced NSCLC either as single modality treatment or with concomitant chemotherapy, advances in understanding of tumor molecular biology and targeted drug development should bring targeted agents into the NSCLC management. The development of numerous therapeutic approaches has made the locally advanced NSCLC world change. An up-to-date overview of the current literature on updated chemotherapeutic agents, targeted therapy, immunotherapy, radiotherapy in stage III NSCLC is provided.